Development of Wide-Compatible Indica Lines by Pyramiding Multiple Neutral Alleles of Indica–Japonica Hybrid Sterility Loci - Guo, Jie; Li, Yun; Xiong, Liang; Yan, Tingxian; Zou, Jinsong; Dai, Ziju; Tang, Guang; Sun, Kangli; Luan, Xin; Yang, Weifeng; Tan, Quanya; Zhu, Haitao; et al. (Frontiers in Plant Science, 2022)
Since indica hybrid rice was developed in the 1970’s, a great success has been achieved in the hybrid rice production in China and in the world. The utilization of inter-subspecific indica-japonica hybrid rice is always expected due to its stronger heterosis. However, there is serious sterility in the indica-japonica hybrid, which hinders the utilization of its heterosis. In the past decades, the genetic basis of indica-japonica hybrid sterility has been well understood. It was found that in indica-japonica hybrid sterility, female sterility was mainly controlled by the S5 locus, and male sterility was mainly controlled by the Sa, Sb, Sc, Sd and Se loci. In this study, we developed wide-compatible indica lines (WCILs) by pyramiding multiple neutral (n) alleles of the hybrid sterility loci. First, we identified Sn alleles of the loci in single-segment substitution lines (SSSLs) in the genetic background of indica Huajingxian 74 (HJX74). Then, the Sn alleles of S5, Sb, Sc, Sd and Se loci in SSSLs were pyramided in the HJX74 genetic background. The WCILs carrying Sn alleles at the S5, Sb, Sc, Sd and Se loci showed wide-compatibility with indica and japonica rice. Therefore, the WCILs will be used to develop inter-subspecific indica-japonica hybrid rice with normal fertility.